2023
DOI: 10.1002/rcm.9596
|View full text |Cite
|
Sign up to set email alerts
|

Review of fragmentation of synthetic single‐stranded oligonucleotides by tandem mass spectrometry from 2014 to 2022

Abstract: The fragmentation of oligonucleotides by mass spectrometry allows for the determination of their sequences. It is necessary to understand how oligonucleotides dissociate in the gas phase, which allows interpretation of data to obtain sequence information. Since 2014, a range of fragmentation mechanisms, including a novel internal rearrangement, have been proposed using different ion dissociation techniques. The recent publications have focused on the fragmentation of modified oligonucleotides such as locked nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The structure of the product ion was proposed to arise from loss of NH from the deprotonated nucleobase. A 2023 review pointed out that the loss of CH 3 • is much more likely but the mass accuracy of the measurement could not distinguish the two. The structure proposed in the review is almost identical to the structure indicated in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the product ion was proposed to arise from loss of NH from the deprotonated nucleobase. A 2023 review pointed out that the loss of CH 3 • is much more likely but the mass accuracy of the measurement could not distinguish the two. The structure proposed in the review is almost identical to the structure indicated in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the product ion was proposed to arise from loss of NH from the deprotonated nucleobase. A 2023 review 63 pointed out that the loss of CH 3…”
Section: Net-cid Of Small Poly-g Ormentioning
confidence: 99%
“…While our approach and the validation data presented in this approach are focused on the detection of the 94.935 m / z product ion, the fragmentation-rich spectra generated via HCD collision offer additional opportunities to target other non-natural modifications present in oligonucleotides that can be successfully extracted and analyzed using our approach. The fragmentation of oligonucleotides in the gas phase has been investigated in great detail for over 30 years [ 15 ]. As there are a large number of natural and non-natural modifications to either the linker, sugar, or base components of a natural or synthetic oligonucleotide, the interpretation of the resulting MS/MS spectra and correct assignment of the sequence without prior knowledge is highly complex, though there are a number of software platforms available to aid in the interpretation [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the number of modifications, including the number of phosphorothioate modifications, found in an oligonucleotide are one factor that influences the ability to detect a particular substance, and the reliance on a single modification for identification may reduce the likelihood for detection, especially if the modification is present in low abundance in the oligo. Further, while the MS/MS scan types employed may provide a large amount of product ions following the fragmentation of the targeted molecule using higher-energy C-trap dissociation, full characterization of the exact sequence of nucleotides is a more challenging endeavor without prior knowledge of the various modifications and exact sequence utilized, though work continues to advance in this area [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry stands as a premier tool for the identification and characterization of biomolecules, encompassing proteins [ 1 , 2 , 3 , 4 ], lipids [ 5 , 6 , 7 , 8 , 9 ], metabolites [ 10 , 11 , 12 , 13 ], glycans [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], DNA [ 23 , 24 , 25 , 26 ], and other small molecules [ 27 ]. In particular, new technologies and methodologies in mass spectrometry have had a tremendous impact on the field of proteomics, providing new insight into protein functions, interactions, localization, and reactivities.…”
Section: Introductionmentioning
confidence: 99%